A DEEP INSIGHT INTO INCIDENCE, PREVALENCE, COMPLETE EPIDEMIOLOGY, AND PREDICTIVE ASSOCIATIONS AMONG MULTIPLE FACTORS OF BREAST CANCER IN KARACHI, PAKISTAN: A CROSS-SECTIONAL SURVEY OF 2023 (Journal of Medical & Health Sciences Review, 2025)
Breast cancer is recognized as a global issue affecting millions of women with a greater impact on their lives. Worldwide, breast cancer is among the most prevalent forms of the disease. Throughout their lives, 12% of American women will experience a breast cancer diagnosis, and in 2017, more than 250,000 new cases were reported to the medical community. This study was conducted in a cross-sectional approach retrospectively in a tertiary care hospital in Karachi, Pakistan, in which data of all types of cancer patients were gathered from 1st January 2023 – 31st December 2023 in a pre-designed/translated data collection form. Initial analysis was piloted in the form of descriptive statistics such as percentages and frequencies. Chi-square tests and Monte Carlo tests were used to analyze breast cancer occurrence and risk factor associations, considering p-value